If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1p + 2 = -1 Reorder the terms: 2 + 1p = -1 Solving 2 + 1p = -1 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 1p = -1 + -2 Combine like terms: 2 + -2 = 0 0 + 1p = -1 + -2 1p = -1 + -2 Combine like terms: -1 + -2 = -3 1p = -3 Divide each side by '1'. p = -3 Simplifying p = -3
| 3(2x+3)=2(3x+1) | | 2a^2-5a-4=0 | | 3u^2+12u+6=0 | | x(x-4)(x+11)=0 | | 4d*-3d= | | (28-4i)-(10-30)=0 | | 3+8x=14-3x | | 1-4(100+36s)=15-4s | | y^2-4y=8 | | 8x+8-ax-a=0 | | 3(x-3)=2(x-2)-(5-3x) | | 0.50(8n-2)=16-30n | | 2x^2+10x-80=0 | | x(2x+3)(x-4)=6 | | x(2x+5)(x-4)=6 | | 9m+5-4m=-20 | | 13x-30=7x-14 | | -6(x-3)=-3(x+9) | | (x-p)(x^2+11x+15)=(x^2-9)(2x+q) | | 2x^2-3-15=0 | | k+84738398=98393398 | | 8+9t=21t-17 | | X^2+.52x=-25 | | 3(b+4b)=40-15+20 | | -4(w-3)-6w=-2(w+6) | | 0=0.4t^2-7.7t+0.5 | | 0.2+10000= | | 3+9*2= | | 2(x-6)+3(2-3x)=5(2x-1)+4x-1 | | 3c+5=4 | | F(x)=x^2-4+6 | | 5(19m-18)=-8-7(-15m-14) |